VISUAL AESTHETIC STUDY BASED ON BUILDING FORM AND MASSING ORGANIZATION CRITERIA ALONG SURAMADU BRIDGE CORRIDOR, SURABAYA - Abitya Indah Rosiani; Ispurwono Soemarno; Haryo Sulistyarso (Journal of Architecture&ENVIRONMENT, 2012)
The existence of Suramadu bridge accelerates transition of building functions, into the function which is economically more valuable. Buildings along this corridor are experiencing visual disharmony order. Therefore, street picture along the corridor should be reorganized to provide visual aesthetic. The purpose of the study is to identify the criteria of building form and massing organization along the corridor in question to achieve better visual aesthetic. This study uses descriptive qualitative method, through exploration of existing data, literatures, stakeholders and users interview, questionnaires, and photographic records. Purposive sampling method is also used to collect samples of stakeholders opinion through interview and questionnaires. As supporting data, samples of users questionnaires are obtained using quota sampling method. After being gathered, the data are systematically analyzed using Delphi analysis techniques. Through these methods, comprehensive criteria required in organizing building form and massing could be established. The results will hopefully be able to accommodate visual aesthetic experience for observers and users at the study area.